Effect of nonwoven filters on rainfall seepage flow and stability of slopes - Koichi Tsubogo; Kohei Araki; Yasushi Fukuda; Keiji Kuwajima; Kosuke Katayama; Shunji Ue (Smart Construction and Sustainable Cities)
Abstract In recent years, the incidence of sediment disasters caused by climate change, such as torrential rains exceeding expectations due to global warming, has been increasing year by year, and the associated human and economic losses have been expanding. In this paper, nonwoven filters were installed on the slope of an on-site observation area in the sediment disaster warning area north of National Institute of Technology, Tokuyama College in Shunan City, Yamaguchi Prefecture. The rainfall intensity and moisture content by volume were then measured in both the nonwoven filter installed and bare ground sections. As a consequence, the relationship between precipitation levels and the occurrence of slope failure was elucidated. Moreover, the rainfall seepage model proposed by Tsubogo et al. demonstrated a reduced discrepancy between the numerical solution and the observed value in comparison to the previous model. When a nonwoven filter was installed, the results of the numerical solutions exhibited a high degree of concordance with the observed value. In the bare ground section, the outcome of the before collapse numerical solution was in alignment with the observed value. However, following the collapse, this concordance exhibited a tendency to diminish.